Special rights in Quran and Sunna and its effect on public life - Kamarudin, Awang Mat; Omar Habes, Ahmed Nawafleh; Nuseibah, YounisBsharat (2019)
Allah (SWT) selected the human being to be his successor in the earth; and prepared for him all what can assist him in this mission. God distinguished him on all other creatures and ridiculed everything in the land for him, and what helps him to build the land to feel privacy in the ownership. This makes him work harder and accomplish more. Thus God; gave this right this right is within the rules of Islamic Shari, and God sent messengers missionaries and forerunners, they defined the rules and clarified them, one of those are the special rights explained by Shari to humans. This study deals with some of the special rights, through the verses of the Holy Quran and the Sunnah. The researcher discussed the effects of special property, the rest of the special rights and the consequent effects on people's lives in general.